2019
DOI: 10.31584/jhsmr.201967
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibiotic Resistance in Escherichia coli from the Fecal Flora of Humans in a Rural Area of Songkhla Province

Abstract: Objective: To determine the prevalence of antibiotic resistance in fecal Escherichia coli (E. coli ) isolated from humans in a rural area of Songkhla province.Meterial and Methods: E. coli strains were isolated from the stool cultures of 75 healthy volunteers in a rural area. Resistance rates for 8 antibiotics were determined.Results: The resistance rates for amoxicillin, doxycyclin, cotrimoxazole, gentamicin and cefazolin were 53.3, 51.3, 24.0, 5.3 and 3.3%, respectively. No resistance to norfloxacin, ceftria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…A report from the Ministry of Public Health in Thailand said that the five most common bacterial species involved in antibiotic resistance were Escherichia coli (E. coli), Klebsiella pneumoniae (K. pneumoniae), Acinetobacter baumannii (A. baumannii), Pseudomonas aeruginosa (P. aeruginosa) and methicillin-resistant Staphylococcus aureus (MRSA) [ 5 ]. A study in southern region of Thailand was reported that the resistance rate for amoxicillin, doxycycline and TMP-SMX were 53.3, 51.3, and 24.0%, respectively [ 22 ]. A community study in Tanzania [ 23 ] found that Escherichia coli strains were mostly present in infections and antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A report from the Ministry of Public Health in Thailand said that the five most common bacterial species involved in antibiotic resistance were Escherichia coli (E. coli), Klebsiella pneumoniae (K. pneumoniae), Acinetobacter baumannii (A. baumannii), Pseudomonas aeruginosa (P. aeruginosa) and methicillin-resistant Staphylococcus aureus (MRSA) [ 5 ]. A study in southern region of Thailand was reported that the resistance rate for amoxicillin, doxycycline and TMP-SMX were 53.3, 51.3, and 24.0%, respectively [ 22 ]. A community study in Tanzania [ 23 ] found that Escherichia coli strains were mostly present in infections and antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%